2016
DOI: 10.1155/2016/2318759
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Spinal Cord Injury during Removal of the Inferior Articular Process in the Presence of Ossification of the Ligamentum Flavum

Abstract: Ossified ligamentum flavum (OLF) is a condition of heterotopic lamellar bone formation within the yellow ligament. Some patients with OLF can be asymptomatic. However, asymptomatic OLF may not be obvious on preoperative MRI and could increase the risk of iatrogenic injury during treatments for unrelated spinal conditions. This report describes a case of spinal cord injury caused by the indirect transmission of force from an osteotome to an asymptomatic OLF during the resection of a thoracic inferior articular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this research, we analyzed the IAPCSA from LS-MRI images and visualized IAP in transverse T1-weighted LS-MRI. LS-MRI provides a high-quality view of the IAP and IAP hypertrophic changes [10,21]. Our research had a few weaknesses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this research, we analyzed the IAPCSA from LS-MRI images and visualized IAP in transverse T1-weighted LS-MRI. LS-MRI provides a high-quality view of the IAP and IAP hypertrophic changes [10,21]. Our research had a few weaknesses.…”
Section: Discussionmentioning
confidence: 98%
“…Because the inferior articular facet meets the superior articular facet at the posterior and medial concavity of the adjoining surface [19], these frictions can exert continuous pressure on zygapophyseal joints and alter morphological features of IAP, leading to a high degree of abrasion [20]. Burke et al have reported a case of spinal cord trauma caused by direct transmission of force from an ostectomy to a symptomatic ossified ligamentum flavum during resection of an IAP [21]. Das et al have reported that an asymmetrical hypertrophy of IAP might be related to disc degeneration and CLSS, and that it may be a cause of buttock and low back pain [22].…”
Section: Discussionmentioning
confidence: 99%